Inverse heat transfer for optimization and on-line thermal properties estimation in composites curing. - Skordos, Alexandros A.; Partridge, Ivana K. (Taylor & Francis, 2004)
Abstract This article presents the development and application of a heat transfer inversion procedure to the cure of thermoset-based composites based on genetic algorithms. The procedure is utilized for process optimization applied to the curing of carbon fiber reinforced composites. The optimization objective is the selection of an appropriate cure schedule so that the duration of the curing is minimized subject to constraints related to the thermal gradients developed during the cure. An alternative use of inversion concerns the integration of monitoring signals with modeling. Inversion is utilized to alter on-line the thermal properties used in the direct model so that monitoring results coincide with simulation predictions. This procedure is applied to the curing of a carbon fiber reinforced thermoset-based composite, using thermal conductivity as the variable thermal property.
Keywords: Composites manufacturing; Optimization; Parameter estimation; Genetic algorithms